Strategi Peningkatan Mutu Pendidikan di TK Permata Bunda - Husna, Nurul (Sekolah Tinggi Ilmu Tarbiyah Syamsul Ma'arif Bontang, 2025)
The purpose of writing this article is to discuss strategies to improve the quality of education, which is one of the important components in the education system. The background of this research is that teachers often face challenges in dealing with children with diverse characteristics. The research methodology used is descriptive qualitative with in-depth interviews with teachers and principals. The results show that Permata Bunda Kindergarten implements several key strategies to improve the quality of education. First, improving teachers' competencies through regular training focused on creative and innovative teaching methods. Second, developing a character-based curriculum that emphasizes moral and social values, as well as skills. Third, improving learning facilities and resources, including the provision of educational teaching aids and play areas. Fourth, active participation of parents in the education process through effective cooperation and communication between schools and parents.